THE STATE AND PROBLEMS OF SERBIAN AGRICULTURE - Vehapi1, Semir; Šabotić, Zenaida (Economics of Agriculture, 2015)
Modern agriculture includes the process of building a new economic activity based on efficiency, competitiveness, intensity and marketability. The process of transition of Serbian agriculture to market conditions is long and difficult. In this study the authors identify the most important problems of this process: unfavorable ownership structure and low productivity, the ineffectiveness of the agrarian and economic policy, the slow development of support institutions and legislative framework, and unsuccessful privatization in agriculture. We are dealing with a number of chronic problems that seriously threaten the development of agriculture and hinder the implementation of transition reforms. The authors propose measures and activities for achieving a transition shift in this strategically important economic branch for Serbia.